Maternal diet during pregnancy and adaptive changes in the maternal and fetal pancreas have implications for future metabolic health - Hill, David J.; Hill, Thomas G. (Frontiers in Endocrinology, 2024)
Fetal and neonatal development is a critical period for the establishment of the future metabolic health and disease risk of an individual. Both maternal undernutrition and overnutrition can result in abnormal fetal organ development resulting in inappropriate birth size, child and adult obesity, and increased risk of Type 2 diabetes and cardiovascular diseases. Inappropriate adaptive changes to the maternal pancreas, placental function, and the development of the fetal pancreas in response to nutritional stress during pregnancy are major contributors to a risk trajectory in the offspring. This interconnected maternal-placental-fetal metabolic axis is driven by endocrine signals in response to the availability of nutritional metabolites and can result in cellular stress and premature aging in fetal tissues, and the inappropriate expression of key genes involved in metabolic control as a result of long-lasting epigenetic changes. Such changes result is insufficient pancreatic beta-cell mass and function, reduced insulin sensitivity in target tissues such as liver and white adipose, and altered development of hypothalamic satiety centres and in basal glucocorticoid levels. Whilst interventions in the obese mother such as dieting and increased exercise, or treatment with insulin or metformin in mothers who develop gestational diabetes, can improve metabolic control and reduce the risk of a large-for-gestational age infant, their effectiveness in changing the adverse metabolic trajectory in the child is as yet unclear.